Regional geoid-model-based vertical datums - some Australian perspectives - Featherstone, Will; Filmer, Michael; Claessens, Sten; Kuhn, Michael; Hirt, Christian; Kirby, Jonathan (Versita, 2012)
This article summarises some considerations surrounding a geoid-based vertical datum that have to be thought through before its implementation and adoption. Our examples are based on many Australian and some South-East Asian experiences, but these probably also apply elsewhere. The key considerations comprise data quality and availability, politics, and difficulties that users may encounter when adopting quite a different approach to height determination. We advocate some form of new vertical datum to replace the Australian Height Datum, but the exact type (whether using levelling or geoid, or some combination of both) still needs to be decided. We are not specifically opposed to the adoption of a geoid model as the vertical datum, but it is possibly more challenging than appears initially, and may even deter some users that are already well served by levelling-based vertical datums.